Understanding the coping process from a self-determination theory perspective - Ntoumanis, Nikos; Edmunds, J.; Duda, J. (John Wiley & Sons Ltd., 2009)
Purpose. To explore conceptual links between the cognitive-motivational- relational theory (CMRT) of coping (Lazarus, 1991) and self-determination theory (SDT) of motivation (Deci & Ryan, 1985). Method. We present a very brief overview of the two theories.We also discuss how components from the two theories can be examined together to facilitate research in the health/exercise domain. To this effect, we offer a preliminary integrated model of stress, coping, and motivation, based on the two aforementioned theories, in an attempt to illustrate and instigate research on how motivational factors are implicated in the coping process. Conclusion. We believe that the proposed model can serve as a platform for generating new research ideas which, besides their theoretical relevance, may have important applied implications. © 2009 The British Psychological Society.